Microbial Applications : Recent Advancements and Future Developments - Carmen Durán-Dominguez-de-Bazua, Maria; Ferreira Filho, Edivaldo X.; Kumar Gupta, Vijai; Purchase, Diane; Zeilinger, Susanne (De Gruyter, 2016)
Microbial applications encompass areas including biotechnology, chemical engineering, and alternative fuel development. Research on their technological developments cover many aspects of work using microbes as cell factories. The fields of biotechnology, chemical engineering, pharmaceuticals, diagnostics and medical device development also employ these microbial products. There is an urgent need to integrate all these disciplines that caters to the need of all those who are interested to work in the area of microbial technologies. This book is a step forward to integrate the aforesaid frontline branches into an interdisciplinary research work quenching the academic as well as research thirst of all those concerned about microbes in the respective area of biotechnology, chemical engineering, and pharmaceuticals. All the chapters in this book are related to important research on microbial applications, written by international specialists for researchers and academics in the concerned disciplines. This publication aims to provide a detailed compendium of experimental work and information used to investigate different aspects of microbial technologies, their products as well as interdisciplinary interactions including biochemistry of metabolites, in a manner that reflects the recent developments of relevance to researchers/scientists investigating microbes.